Diversifikasi Produk Pengolahan Pisang dalam Upaya Menambah Ketrampilan Berwirausaha Bagi Kaum Perempuan GMIT Imanuel Oepunu - Yudith Febrianty Lerrick; Melvin Krisdiana Djami Rane (Jurnal Pengabdian Masyarakat, 2024)
Bananas are a horticultural commodity (fruit) that is easily damaged, so efforts must be made to make them last longer, such as processing them into banana chips. Banana plants in the congregation in the GMIT Imanuel Oepunu service area and the fruit are only used for household consumption. Many bananas are also wasted, only becoming animal feed. Therefore, it would be better if the women's congregation of GMIT Imanuel Oepunu could diversify banana products into food products with higher sales value to increase the congregation’s household income. In addition to processing banana products, the team also makes product packaging that is given a label to provide information about the banana chips product in the form of pictures and the writing of the GMIT Imanuel Oepunu banana chips product brand.